International Law and International Relations: a Problematic and/or a Harmonious Relationship (Annual of the Faculty of Philosophy in Skopje, 2018)
The paper focuses on the relationship between International Law and InternationalRelations, i.e. on their interconnectedness as a substantial issue both from theoreticaland practical point of view. The starting premise is that although they constitute distinctacademic disciplines, the objects of their interest can hardly be analysed in isolation fromeach other. Even those who disagree with the thesis of their academic synergy, acknowledgethat with no international law there could be no international relations; also, the practiceof international politics is a ground that breeds international legal norms. In the analysisof this rather complex relationship, a special emphasis is placed on the need for deconstructionof the wide-spread myth that international law is by default ‘good’ (i.e. positive ina normative sense of the word), while the international politics is to be blamed for all thebad things that happen in the international arena. Instead, we make an attempt to shedsome light on the most important strategic and moral limits of the international law, in orderto induce a more critical viewpoint on the relations between power, politics and law inthe international arena. The paper ends with some suggestions about the need for developmentof an innovative research agenda in elaboration of this relationship.
Keywords: INTERNATIONAL LAW; INTERNATIONAL RELATIONS; INTERNATIONAL POLITICS; ETHICS; CRITICAL STUDIES